Gene expression profiling of patient‐derived pancreatic cancer xenografts predicts sensitivity to the BET bromodomain inhibitor JQ1: implications for individualized medicine efforts. Issue 4 (8th March 2017) - Bian, Benjamin; Bigonnet, Martin; Gayet, Odile; Loncle, Celine; Maignan, Aurélie; Gilabert, Marine; Moutardier, Vincent; Garcia, Stephane; Turrini, Olivier; Delpero, Jean‐Robert; Giovannini, Marc; Grandval, Philippe; et al.
Abstract: c‐MYC controls more than 15% of genes responsible for proliferation, differentiation, and cellular metabolism in pancreatic as well as other cancers making this transcription factor a prime target for treating patients. The transcriptome of 55 patient‐derived xenografts show that 30% of them share an exacerbated expression profile of MYC transcriptional targets (MYC‐high). This cohort is characterized by a high level of Ki67 staining, a lower differentiation state, and a shorter survival time compared to the MYC‐low subgroup. To define classifier expression signature, we selected a group of 10 MYC target transcripts which expression is increased in the MYC‐high group and six transcripts increased in the MYC‐low group. We validated the ability of these markers panel to identify MYC‐high patient‐derived xenografts from both: discovery and validation cohorts as well as primary cell cultures from the same patients. We then showed that cells from MYC‐high patients are more sensitive to JQ1 treatment compared to MYC‐low cells, in monolayer, 3D cultured spheroids and in vivo xenografted tumors, due to cell cycle arrest followed by apoptosis. Therefore, these results provide new markers and potentially novel therapeutic modalities for distinct subgroups of pancreatic tumors and may find application to the future management of these patients within the setting of individualized medicine clinics. Synopsis: c‐MYC controls the expression of a large panel of target genes that characterize tumor phenotypes. Sustained growth and aggressivity of a subgroup of pancreatic ductal adenocarcinoma (PDAC) strongly depend on the level of the transcriptional program of c‐MYC. A 16‐transcript signature discriminates a MYC‐dependent (MYC‐high) PDAC subgroup in a learning cohort of 55 patient‐derived xenografts. MYC‐high tumors are highly proliferative and undifferentiated compared to MYC‐low tumors. MYC‐high tumors are more sensitive to JQ1 treatment, a well‐described bromodomain inhibitor. Abstract : c‐MYC controls the expression of a large panel of target genes that characterize tumor phenotypes. Sustained growth and aggressivity of a subgroup of pancreatic ductal adenocarcinoma (PDAC) strongly depend on the level of the transcriptional program of c‐MYC.